Effects of anthropogenic fragmentation on the biodiversity of plants in northern meadow steppes - Bakka Sergey (EDP Sciences, 2021)
The paper is aimed to assess the effect of anthropogenic fragmentation on the biodiversity of plants in northern meadow steppes located in the southeast of the Nizhny Novgorod region. The plants were chosen as a model group. A quantitative analysis of the dependence of the number of species on the area of habitats was carried out according to the data collected at 158 sites of meadow steppes and steppe meadows with a total area of 10752 ha. For each of the meadow steppe and steppe meadows surveyed, the total area, proportion, and area covered with meadow steppe communities proper were determined, and a floristic list was compiled, in which species characteristic of meadow steppes were identified. Totally flora lists 361 species of plants, including 110 steppe species. It is shown that ecological interactions between separate fragments of meadow steppe in the south-east of Nizhny Novgorod region are broken; the remained fragments of meadow steppe are isolated. To conserve biological diversity in the forest-steppe zone, the special measures aimed at the ecological restoration of interactions between meadow steppe fragments is necessary.